THE RADZIWIŁŁS AS ORATORS IN THE 16TH AND 17TH CENTURIES – INTRODUCTION - Jarczykowa, Mariola (Prace Polonistyczne, 2021)
The article focuses on the representatives of the Radziwiłł family whose speeches were published in print or recorded in diaries and copiers of the 16th, 17th and 18th centuries. Many, often emotional orations of Mikołaj “the Black”, who presented them at the Parliament meetings, have survived. In his speeches he made many references to proverbs, literature, and the Bible. Prince Krzysztof of the Birża line was the most famous orator of the 17th century. He not only delivered speeches about state affairs, but also spoke at funerals and weddings. His oratory skills were recognised and praised by many contemporaries. Prince Krzysztof educated his son Janusz and his nephew Bogusław in rhetoric. Both of them gave public speeches when they were still very young. Yet, their speeches – with some minor exceptions – were not popular. Chancellor Albrycht Stanisław of the Nieśwież line was another well-known speaker who, due to his position, delivered a number of public speeches and evaluated other orators’ skills in his diary. Many speeches by Michał Kazimierz Radziwiłł have survived, preserved in a manuscript and in print (they were published in the 18th century by Johann Christian Lünig). Another anthology featuring many speeches by the Radziwiłłs was collected and edited by Jan Ostrowski-Daneykowicz. At the end of the 17th century, the following members of the Radziwiłł family gave speeches at the parliament: Dominik Mikołaj and Karol Stanisław, who actively participated in the parliamentary sessions of the Warsaw Sejm in 1690. In their speeches they not only supported the policy of King Jan III Sobieski, but also defended the Radziwiłł family.